Graphology in German psychiatry (1870–1930). Issue 3 (September 2016) - Schäfer, Armin
This article discusses both the use of graphology in German psychiatry (1870–1930) and the use of handwriting in psychiatric experiments. The examination of handwriting was part of an ensemble of diagnostic tools. Although disorders of handwriting seemed to indicate psychic diseases, graphology did not seem the right method to produce valid observations. Nevertheless, psychiatrists began to incorporate the process of writing into research and diagnosis and to make the process of handwriting an experimental field. Emil Kraepelin invented an apparatus – the so-called Writing-Scale – with which he could measure the dynamics of writing in various dimensions and, in particular, the pressure of movements. The experiments produced a huge amount of data, but the psychiatrists were unable to interpret them in a comprehensible way. Although psychiatrists failed to grasp the psychopathology in handwriting, they discovered a systemic behaviour of the organism controlled by feedback.